From the Editor-in-Chief: It's Spring and Convocation is in the Air. So What? - Dorothy Pringle (Nursing Leadership, 2004)
As I write this editorial, the sun is shining and we are having a beautiful warm summer-like day. The second in a row - a record of sorts for this spring! Now, why am I giving you a weather report? First, I am Canadian and can justify talking about the weather just about any time. But, spring and sunny days also bring convocation to mind. Thousands of student nurses have just graduated or will graduate over the next month and join the workforce. This is a particularly momentous year in Ontario because the last class of nurses prepared at the diploma level will graduate from community colleges. Next year all nursing graduates in that province will have a degree and the majority of graduates will have completed collaborative programs jointly offered by colleges and universities. By next year, with the exception of Quebec, one program in Manitoba, one in the Northwest Territories and a few graduates in B.C. and Alberta, who choose to graduate after three years with a diploma rather than a degree, Canada will be close to achieving what few other countries have managed, the conversion of nursing education from a diploma to a degree base.